La création de pages Internet dans le cadre de parcours individualisé : la place de la méthodologie dans l'apprentissage des langues. - Joline Boulon (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication, 1998)
On line language projects suggest worthwhile steps to take for overall comprehension work, which is why we have chosen to use projects to develop a specific methodology for tasks that we have our learners do. However, comprehensible input is insufficient for learning all of the language skills. Work that never demands an analysis of language structure or form cannot make learners sufficiently aware of the language in order to have their interlanguage develop. It seems to us that projects should include a very specific methodology that allows learners to work on precision as well as overall comprehension. We discuss an example of the pages we are in the process of creating on Internet.